2020
DOI: 10.1021/acs.jpcc.0c04639
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Electronic Properties of Highly Mn-Doped β-NaGdF4 and β-NaEuF4 Nanoparticles with a Narrow Size Distribution

Abstract: We have performed a detailed study of the magnetic and electronic properties of highly manganese-doped β-NaGdF4 and β-NaEuF4 nanoparticles with a narrow size distribution. XPS as well as XRF experiments confirm the successful doping of 11 ± 2% Mn into β-NaGdF4 and β-NaEuF4 nanoparticles, i.e., a much higher Mn concentration than has been previously reported for the incorporation of bivalent transition metal ions into the β phase of NaREF4 (RE = rare earth) nanocrystals. Owing to the high manganese concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…At the parts per billion level, the EPR signal of Mn 2+ should exhibit a well-resolved 6-fold fine spectral line with g ≈ 2.0, which is characteristic of the hyperfine structure of Mn 2+ in manganese-containing standard samples, arising from the dipole–dipole interaction between the electron spin and magnetic moment. When the Mn 2+ concentration escalates to a certain threshold, a single broad line is discernible in the EPR spectrum. , Given that the Mn 2+ ion content in UCNPs exceeds the ppb level, its EPR signal presents a broad peak with g ≈ 2.0 and line width congruent with the six fine spectral lines of manganese-containing standard samples (as depicted in Figure a), substantiating the successful integration of Mn 2+ ions into UCNPs. The binding energies of Mn 2p 3/2 and Mn 2p 1/2 core energy levels are 654.0 and 642.1 eV, respectively, closely aligning with the spectrum of MnF 2 (as demonstrated in Figure b), signifying the successful doping of Mn 2+ ions into UCNPs .…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…At the parts per billion level, the EPR signal of Mn 2+ should exhibit a well-resolved 6-fold fine spectral line with g ≈ 2.0, which is characteristic of the hyperfine structure of Mn 2+ in manganese-containing standard samples, arising from the dipole–dipole interaction between the electron spin and magnetic moment. When the Mn 2+ concentration escalates to a certain threshold, a single broad line is discernible in the EPR spectrum. , Given that the Mn 2+ ion content in UCNPs exceeds the ppb level, its EPR signal presents a broad peak with g ≈ 2.0 and line width congruent with the six fine spectral lines of manganese-containing standard samples (as depicted in Figure a), substantiating the successful integration of Mn 2+ ions into UCNPs. The binding energies of Mn 2p 3/2 and Mn 2p 1/2 core energy levels are 654.0 and 642.1 eV, respectively, closely aligning with the spectrum of MnF 2 (as demonstrated in Figure b), signifying the successful doping of Mn 2+ ions into UCNPs .…”
Section: Resultsmentioning
confidence: 64%
“…When the Mn 2+ concentration escalates to a certain threshold, a single broad line is discernible in the EPR spectrum. 46,47 Given that the Mn 2+ ion content in UCNPs exceeds the ppb level, its EPR signal presents a broad peak with g ≈ 2.0 and line width congruent with the six fine spectral lines of manganese-containing standard samples (as depicted in Figure 2a), substantiating the successful integration of Mn 2+ ions into UCNPs. The binding energies of Mn 2p 3/2 and Mn 2p 1/2 core energy levels are 654.0 and 642.1 eV, respectively, closely aligning with the spectrum of MnF 2 (as demonstrated in Figure 2b), signifying the successful doping of Mn 2+ ions into UCNPs.…”
Section: Resultsmentioning
confidence: 64%
“…The results showed that the magnetic properties of the nanoparticles can be controlled by adjusting the doping concentration of Gd 3+ , which makes it have broad application prospects in MRI. 34,35…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…In particular, the combination of rare-earth ions (RE 3+ ) and Mn 2+ in UCNP systems. [104][105][106] For instance, Wang et al 107 reported that Mn 2+ co-doping can enable NaGdF 4 :Yb 3+ ,Er 3+ nanoparticles to exhibit superparamagnetic properties. In their studies, they showed that as the concentration of Mn 2+ ion increases, the paramagnetic property (due to Gd 3+ ) changes, causing a transition from a paramagnetic to a super-paramagnetic state.…”
Section: Improvement Of Magnetic Properties In Lanthanide Upconversio...mentioning
confidence: 99%